Monitoring of outdoor tourism demand. North of Portugal - Martins, Oliva M. D. (2022)
The Herfindahl-Hirschman Index (HHI) was used in order to understand the tourism competitiveness of the different sub-regions that make up the North Region of Portugal. This index is a measure which helps to analyse market concentration and at the same time determines the competitiveness of the market.